2022
DOI: 10.3389/fcell.2022.862675
|View full text |Cite
|
Sign up to set email alerts
|

CXC Chemokine Receptor 2 Accelerates Tubular Cell Senescence and Renal Fibrosis via β-Catenin-Induced Mitochondrial Dysfunction

Abstract: Renal fibrosis is a common feature of various chronic kidney diseases (CKD). However, its underlying mechanism has not been totally clarified. C-X-C motif chemokine receptor (CXCR) family plays a role in renal fibrosis, however, detailed mechanisms have not been elucidated. Here, we report that CXCR2 has a potential role in tubular cell senescence and renal fibrosis, and is associated with β-catenin-activated mitochondrial dysfunction. CXCR2 is one of most increased members among CXCR family in unilateral uret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Analysis of existing single nuclear RNAseq of injured mouse kidneys indicates that Cxcl5 is highly expressed in different segments of nephron epithelial cells, while Cxcr2 is highly expressed in epithelial cells, immune cells and interstitial cells 90,91 . Inhibition of Cxcr2 protects against tubular cell senescence and renal fibrosis following unilateral ureteral obstruction (UUO) 92 , and reduces kidney injury associated with a reduction of inflammatory cytokines and neutrophils infiltration 93 . Intriguingly, it was shown that liver cysts of ADPKD patients secrete agonists of Cxcr2, which promote cell proliferation and cyst growth 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of existing single nuclear RNAseq of injured mouse kidneys indicates that Cxcl5 is highly expressed in different segments of nephron epithelial cells, while Cxcr2 is highly expressed in epithelial cells, immune cells and interstitial cells 90,91 . Inhibition of Cxcr2 protects against tubular cell senescence and renal fibrosis following unilateral ureteral obstruction (UUO) 92 , and reduces kidney injury associated with a reduction of inflammatory cytokines and neutrophils infiltration 93 . Intriguingly, it was shown that liver cysts of ADPKD patients secrete agonists of Cxcr2, which promote cell proliferation and cyst growth 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was performed with routine protocol [ 72 ]. Frozen kidney sections (3 μm) were fixed with 4% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%
“…TRPC6 channel also affects components of the innate immune response. It has been reported that TRPC6 channels regulate CXC chemokine receptor 2 (CXCR2)-related chemotaxis by mediating Ca 2+ influx ( Lindemann et al, 2013 ), promoting renal tubular cell senescence and renal fibrosis by inducing mitochondrial dysfunction ( Meng et al, 2022 ). Interestingly, Klotho, a single-channel type 1 transmembrane protein with anti-renal fibrotic effects, had no effect on obstruction-induced fibrosis in TRPC6 knockout mice, suggesting that the renal protective effect of Klotho in UUO is partly mediated through inhibition of TRPC6 ( Satoh et al, 2012 ; Wu et al, 2017b ).…”
Section: Ca 2+ Channelsmentioning
confidence: 99%